The Routledge Handbook of Philosophy and Science of Addiction - Pickard, Hanna (Taylor & Francis, 2019)
The problem of addiction is one of the major challenges and controversies confronting medicine and society. It also poses important and complex philosophical and scientific problems. What is addiction? Why does it occur? And how should we respond to it, as individuals and as a society?